Pengaruh Senam Ergonomik Terhadap Tingkat Nyeri Pada Lansia Penderita Rheumatoid Arthritis Di PSTW Budi Mulia 1 Cipayung Tahun 2023 - Saiful Gunardi; Devara Sari Febrianty; Weslei Daeli (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
As age changes, without realizing it, elderly people will also experience physical, psychosocial and spiritual changes. One of these changes is cardiovascular and musculoskeletal disorders. Musculoskeletal system disorders are a factor in chronic diseases and motor system disorders in the elderly such as rheumatoid arthritis. Rheumatoid Arthritis is at risk of causing complications in the form of carpal tunnel syndrome, a condition that causes numbness, tingling, pain or weakness. on the hands and wrists. This research uses a quantitative research design using a one group pre-post test (pre-experimental) method. A quantitative design is used because the data will be used to determine the influence between variables which are expressed using numbers or a numerical scale. The sampling technique used purposive sampling with a sample size of 20 respondents. Data analysis used paired t test t test. shows that from the results of the dependent t test or paired sample T-test, it can be seen that the average level of pain before and after doing ergonomic exercises is 1,650 and obtained P value = 0.000 < 0.05, so H0 is rejected, meaning that there is an influence of ergonomic exercises on pain levels in elderly people suffering from rheumatoid arthritis at PSSW Budi Mulia 1 Cipayung in 2023